Histological Effect of Ultra Violet (UV) Light on the Brain of Albino Wistar Rats - Uwuigbe Mathew; Ohiwerei Wisdom Omogbai; Edebiri Ogbemudia; Ajanwachukwu; Ogbonna Wilson (MultiTech Publisher, 2024)
UV light, or ultraviolet light, is a type of radiation that falls between the visible light and X-ray regions of the electromagnetic spectrum. It is a form of electromagnetic radiation emitted by the sun and artificial sources, such as tanning beds and UV lamps. It has a shorter wavelength than visible light, ranging from 100 to 400 nanometers (nm). It is categorized into three types based on their wavelengths: UVA, UVB, and UVC. The aim of this study is to evaluate the histopathological effect of uv light on the brain of adult Wistar albino rats. In all, fifty (50) adult Albino Wistar rats were used for this study. Group A served as the control and the rats were given distilled water. Animals in the test groups (B, C, D and E) were exposed to 30mins, 1hr, 2hrs and 4hrs of UV lights. After the administration, the rats were put under light chloroform anaesthesia and the brain harvested for histological processing. Short-term exposure (30 min daily) did not cause significant changes, whereas prolonged exposure (1 to 4 hours daily) led to pronounced gliosis, neuronal congestion, and axonal alterations. These findings suggest that chronic UV radiation exposure can have detrimental effects on neural integrity, possibly through oxidative stress, DNA damage, and vascular compromise. The long-term implications of these findings may extend beyond structural damage to include cognitive and behavioral deficits, underscoring the need for further investigations